PENERAPAN ANALISIS REGRESI DATA PANEL PADA INDEKS PEMBANGUNAN MANUSIA DI PROVINSI PAPUA BARAT - Desti Setya Ningsih; Esther Ria Matulessy; Dariani Matualage (FMIPA Universitas Papua, 2020)
Panel Data Regression Analysis is a combination of time series data and cross section data. The purpose of this study is to determine the best model for panel data regression analysis on HDI in West Papua Province and to determine the HDI model in West Papua Province. The data used in this study are West Papua data in the 2019 Publication Figures and 2019 Publication Human Development Index data. In the process of determining the best model, estimating model parameters with 3 approaches namely CEM, FEM and REM, then testing model selection, classical assumption test, model equation checking and finally model interpretation. The results of this study indicate that the best regression model is FEM with individual effects and time effects with a good model of 91% which means that HDI in West Papua Province is explained by GRDP, RLS, JPM and UHH. The equation model is as follows: Based on the equations that have been obtained, the variables that have a significant effect on HDI in West Papua Province are RLS and UHH.